Strategi Pengembangan Usaha UMKM Kue Tradisional: Studi Kasus Usaha Kue RAHEL di Tanah Datar - Jefica Septriana; Novadilastri Novadilastri; Sularno Sularno (CV. ITTC INDONESIA, 2025)
This article discusses the development strategy of UMKM (Micro, Small, and Medium Enterprises) in traditional snack businesses, with a case study of Kue RAHEL in Tanah Datar. The purpose of this research is to analyze the strengths, challenges, and opportunities of UMKM in maintaining traditional culinary heritage while expanding its market. The research method used is descriptive qualitative through observation, documentation, and interviews with business owners. The results show that UMKM RAHEL has unique strengths in taste, cultural value, and local ingredients, but faces challenges in digital marketing and production capacity. This study highlights the importance of innovation, branding, and the use of digital platforms to increase competitiveness in the modern era. The findings are expected to serve as a reference for other traditional snack businesses in Indonesia.